Revisiting the Zimbabwean Unfair Labour Practice Concept - Tapiwa Givemore Kasuso (Potchefstroom Electronic Law Journal, 2021)
The 2013 Constitution of Zimbabwe entrenches the broad right to fair labour practices. The right is given effect to in Part III of the Labour Act (Chapter 28:01), which provides an exhaustive list of unfair labour practices which can be committed by employers, trade unions, workers' committees, and other persons. The Labour Act predates the 2013 Constitution. The constitutionalisation of the right to fair labour practices necessarily carries with it the attendant difficulties of reconciling the new rights and the pre-existing regulatory framework. This article seeks to contribute towards a practical understanding of the Zimbabwean unfair labour practice concept in the light of the constitutionalisation of the right to fair labour practices. It explores the nature and scope of the concept of unfair labour practice and examines its relationship with the constitutional right. Further, the contribution critiques the formalistic and conservative approach adopted by the Constitutional Court in explaining this relationship. The article commences with a brief discussion of the origins of the concept and its reception in Zimbabwean labour law. Following from this, the contribution critically analyses the unfair labour practice concept from statutory and constitutional perspectives. It argues for an expanded paradigm of the concept. This can be achieved if the judiciary moves away from pedantic approaches to the interpretation of labour rights. Therefore, the clarion call is for a purposive and expansive interpretation of the right to fair labour practices, which promotes constitutionalism. In addition, the contribution calls upon the legislature to reconsider the viability of the exhaustive list of unfair labour practices in Part III of the Labour Act, given the constitutionalisation of the broad right to fair labour practices.